A microbial ecosystem beneath the West Antarctic ice sheet - B. C. Christner; J. C. Priscu; A. M. Achberger; S. P. Carter; K. Christianson; A. B. Michaud; J. A. Mikucki; A. C. Mitchell; M. L. Skidmore; Trista J. Vick Majors; BARBANTE, Carlo (Nature, 2014)
Liquid water has been known to occur beneath the Antarctic ice sheet for more than 40 years, but only recently have these subglacial aqueous environments been recognized as microbial ecosystems that may influence biogeochemical transformations on a global scale. Here we present the first geomicrobiological description of water and surficial sediments obtained from direct sampling of a subglacial Antarctic lake. Subglacial Lake Whillans (SLW) lies beneath approximately 800 m of ice on the lower portion of the Whillans Ice Stream (WIS) in West Antarctica and is part of an extensive and evolving subglacial drainage network. The water column of SLW contained metabolically active microorganisms and was derived primarily from glacial ice melt with solute sources from lithogenic weathering and a minor seawater component. Heterotrophic and autotrophic production data together with small subunit ribosomal RNA gene sequencing and biogeochemical data indicate that SLW is a chemosynthetically driven ecosystem inhabited by a diverse assemblage of bacteria and archaea. Our results confirm that aquatic environments beneath the Antarctic ice sheet support viable microbial ecosystems, corroborating previous reports suggesting that they contain globally relevant pools of carbon and microbes that can mobilize elements from the lithosphere and influence Southern Ocean geochemical and biological systems. © 2014 Macmillan Publishers Limited. All rights reserved.